(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study was conducted to verify the effects that flipped learning classes have on the satisfaction with classes after applying flipped learning classes to university students of nursing Method/Statistical Analysis: This study is a descriptive and investigative study that verifies the effects of flipped learning on satisfaction with classes, after applying flipped learning to the course of nursing management for university students of nursing. Findings: Through this study, it was found that factors affecting the satisfaction with flipped learning classes were learning attitude and satisfaction with the subject. Improvements/Applications: In order to improve the satisfaction of learners during flipped learning classes, measures to improve learning attitude and the satisfaction with the subject would be needed.